2017
DOI: 10.1038/s41598-017-08335-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between LRP1 C766T polymorphism and Alzheimer’s disease susceptibility: a meta-analysis

Abstract: Low density lipoprotein receptor-related protein 1 (LRP1) C766T polymorphism (rs1799986) has been extensively investigated for Alzheimer’s disease (AD) susceptibility. However, results in different studies have been contradictory. Therefore, we conducted a meta-analysis containing 6455 AD cases and 6304 controls from 26 independent case–control studies to determine whether there was an association between the LRP1 C766T polymorphism and AD susceptibility. The combined analysis showed that there was no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…This SNP is reported to be associated with susceptibility to Alzheimer’s disease, supporting its functional significance. 25 Of note, while the predictive value of ANXA1 rs1050305 was consistently validated on OS, that of LRP1 rs1799986 was observed on inconsistent clinical outcomes between the discovery and validation cohorts: the discovery cohort showed a significant association with OS, and the validation cohort showed that with PFS. This discrepancy might be due to some unidentified factors such as different contribution of second-line treatment between two cohorts, which might affect the associations between biomarker and clinical outcome.…”
Section: Discussionmentioning
confidence: 96%
“…This SNP is reported to be associated with susceptibility to Alzheimer’s disease, supporting its functional significance. 25 Of note, while the predictive value of ANXA1 rs1050305 was consistently validated on OS, that of LRP1 rs1799986 was observed on inconsistent clinical outcomes between the discovery and validation cohorts: the discovery cohort showed a significant association with OS, and the validation cohort showed that with PFS. This discrepancy might be due to some unidentified factors such as different contribution of second-line treatment between two cohorts, which might affect the associations between biomarker and clinical outcome.…”
Section: Discussionmentioning
confidence: 96%
“…We selected five SNPs (DVL1 rs61735963, WNT16 rs2908004, ITIH5 rs10795550, LRP1 rs1799986 and SFRP1 rs1127379) and investigated their association with OA risk in a Chinese population. Two SNPs (WNT16 rs2908004 and LRP1 rs1799986) were reported . WNT16 could influence bone mineral density (BMD), cortical bone thickness and osteoporotic fracture risk .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibited shedding of low‐density LRP1 reversed the cartilage matrix degradation in OA . The role of LRP1 rs1799986 polymorphism was studied in various diseases, including cardiovascular disease and Alzheimer's disease (AD) . LRP1 rs1799986 polymorphism was associated with lower risk of AD among Asians and could reduce risk of late onset of AD, as revealed by a meta‐analysis containing 6455 AD cases and 6304 controls .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation